Farmer's acceptance towards fragrant rice farming: the case of non-granary areas in the East Coast, Malaysia - Jamal, Kasazlinda; Kamarulzaman, Nitty Hirawaty; Abdullah, Amin Mahir; Ismail, Mohd Mansor; Hashim, Marzukhi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Malaysia depends on imports for its fragrant rice, mostly from Thailand, Vietnam, India and Pakistan. The fragrant rice farming in non-granary areas has been included in the new Entry Point Project (EPP) under the National Key Economic Areas (NKEA). In order to realize the aspiration of producing fragrant rice in large areas, it would require full participation and commitment from the existing and new farmers. The objective of this paper is to investigate farmer's acceptance towards fragrant rice farming in two districts namely Pasir Mas and Tanah Merah, located in the state of Kelantan. The respondents of the study are 23 farmers and in-depth interviews are carried out to obtain farmers' responses towards fragrant rice farming. The results from the content analysis reveal innovation characteristics, extension services and market pressure are among several factors that explain farmers' acceptance towards fragrant rice farming.